Depression, disturbed eating behavior, and metabolic control in teenage girls with type 1 diabetes. Issue 5 (19th February 2013) - Colton, Patricia A; Olmsted, Marion P; Daneman, Denis; Rodin, Gary M
Abstract : Background: Depression and disturbed eating behavior (DEB) are more common in girls with type 1 diabetes (T1D) than in the general population, and may negatively affect metabolic control. Objective: To examine the relationship among depression, DEB, and metabolic control in teenage girls with T1D. Methods: Metabolic control, body mass index and interview‐ascertained symptoms of depression, and DEB were assessed twice in 98 girls with T1D, 9–14 y at baseline and 5 yr later at 14–18 yr. Results: At year 5, 12.2% of girls reported current depressive symptoms, 49.0% reported current DEB, and 13.3% had a full or subthreshold eating disorder (ED). Eating Disorder Examination score was higher in girls with depression (1.4 ± 1.3 vs. 0.5 ± 0.7; p = 0.03), and 75.0% of girls with depression also endorsed DEB vs. 45.3% of girls without depression (p = 0.05). Girls with an ED were at high risk for depressive symptoms; 69.2% reported depressive symptoms vs. 22.0% of girls with no DEB (p = 0.004). Metabolic control was not significantly associated with either depression or DEB in this cohort. A regression model using baseline and year 5 depression and DEB to predict year 5 hemoglobin A1c was not significant overall. Conclusions: Depression and DEB were common and frequently concurrent in this cohort. It was encouraging that poor metabolic control was not yet strongly associated with either depression or DEB. Early detection and treatment may help to prevent the development of entrenched difficulties in this triad of mood, eating behavior, and metabolic control in a vulnerable population.